2018
DOI: 10.1001/jama.2018.0030
|View full text |Cite
|
Sign up to set email alerts
|

Association of the Affordable Care Act Dependent Coverage Provision With Prenatal Care Use and Birth Outcomes

Abstract: In this study of nearly 3 million births among women aged 24 to 25 years vs those aged 27 to 28 years, the Affordable Care Act dependent coverage provision was associated with increased private insurance payment for birth, increased use of prenatal care, and modest reduction in preterm births, but was not associated with changes in cesarean delivery rates, low birth weight, or NICU admission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 38 publications
0
27
0
Order By: Relevance
“…There is limited research on this association among women with commercial health insurance, who account for almost half of all births [18]. The proportion of births covered by commercial health insurance, particularly after the implementation of the Affordable Care Act (ACA), is growing [38,39]. This study showed that despite access to commercial health insurance coverage, women who resided in areas with higher deprivation were at greater odds of preterm birth.…”
Section: Strengths and Limitationsmentioning
confidence: 95%
“…There is limited research on this association among women with commercial health insurance, who account for almost half of all births [18]. The proportion of births covered by commercial health insurance, particularly after the implementation of the Affordable Care Act (ACA), is growing [38,39]. This study showed that despite access to commercial health insurance coverage, women who resided in areas with higher deprivation were at greater odds of preterm birth.…”
Section: Strengths and Limitationsmentioning
confidence: 95%
“…Although the ACA did not alter Medicaid coverage during pregnancy [32], we found that the ACA's Medicaid expansion was associated with a significant increase in medications for OUD among pregnant women with a criminal justice agency or individual referral in expansion states compared with nonexpansion states. There are several possible explanations for this finding.…”
Section: Plos Medicinementioning
confidence: 62%
“…Current literature examining the influence of nonpregnancy Medicaid expansion on maternal health care use in the overall population has mixed findings. 23 , 24 , 25 , 26 , 27 , 28 Our analysis builds on this research with a new focus on a large proportion of birthing individuals not eligible for Medicaid in most areas in the US.…”
Section: Discussionmentioning
confidence: 99%